2020
DOI: 10.1016/j.foodres.2020.109281
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal variation of bioactive properties and phenolic composition of Cynara cardunculus var. altilis

Abstract: Cynara cardunculus L. (cardoon) has several health benefits mainly attributed to its abundance in polyphenols. In this study, cardoon heads (capitula) were harvested in Greece during the flowering stage, and the hydroethanolic extracts were assessed in terms of phenolic compounds composition and antioxidant, cytotoxic, anti-inflammatory, and antimicrobial activities. The phenolic profile was evaluated by HPLC-DAD-ESI/MS to better understand the seasonal changes in the individual compound levels and how these c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
46
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 21 publications
(53 citation statements)
references
References 33 publications
7
46
0
Order By: Relevance
“…Sample Car B was the only sample with a PUFA/SFA value higher than 0.45 and an n-6/n-3 ratio value lower than 4.0, both characteristics being associated with good nutritional properties. This evidence agrees with the popular medicine, since in the Mediterranean cousin cardoon heads are used when immature [19,42,43]. With the results obtained in this study, we corroborate the consumption of immature cardoon heads, preferably harvested in the beginning of May, based on the conditions of the growing location.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Sample Car B was the only sample with a PUFA/SFA value higher than 0.45 and an n-6/n-3 ratio value lower than 4.0, both characteristics being associated with good nutritional properties. This evidence agrees with the popular medicine, since in the Mediterranean cousin cardoon heads are used when immature [19,42,43]. With the results obtained in this study, we corroborate the consumption of immature cardoon heads, preferably harvested in the beginning of May, based on the conditions of the growing location.…”
Section: Discussionsupporting
confidence: 91%
“…In a previous study, we studied the bioactive properties of cardoon heads also analyzed in the present work and despite the antioxidant capacity associated with tocopherols, the anticipation that the sample Car B with the highest tocopherols content would show the greater antioxidant activity was not verified. This fact suggests that other classes of compounds, such as phenolic compounds, could be also related to the demonstrated antioxidant potential [19], while Kukić et al [44] suggested that β-sitosterol possessed a strong antioxidant capacity in extracts obtained from cardoon bracts. Despite that, the highest content of α-tocopherol in this sample could be associated with the highest content in PUFAs (see Table 2) highlighting the protective effects of tocopherols against lipid peroxidation [45,46].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, although the sample C8 had a higher content in tocopherols and was more efficient to inhibit oxidative hemolysis (OxHLIA), the same was not true for the inhibition of lipid peroxidation (thiobarbituric acid reactive substances; TBARS), where sample C1 revealed a superior antioxidant potential [32]. The same observation was also made in samples of cardoon heads [40], suggesting that other classes of compounds are involved in the antioxidant capacity demonstrated by the analyzed samples. Moreover, it is very common in natural matrices to exhibit variable effectiveness in various antioxidant activity assays, since different compounds and mechanisms are involved in different assays [41,42].…”
Section: Tocopherols Organic Acids and Free Sugars Contentmentioning
confidence: 72%